2022
DOI: 10.1002/fsn3.2706
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the gel properties, microstructural characteristics, and intermolecular forces of soybean protein isolate gel induced by transglutaminase

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 55 publications
(98 reference statements)
1
8
0
Order By: Relevance
“…Hydrophobic interactions are the main forces that maintain the tertiary structure of proteins, and they play an important role in the stability, conformational, and functional properties of protein structures. Surface hydrophobicity is the main physical parameter for evaluating proteins and it better reflects the interaction of proteins with water and other chemical groups 30 . The ANS fluorescence probe is a classical method to evaluate the surface hydrophobicity of proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrophobic interactions are the main forces that maintain the tertiary structure of proteins, and they play an important role in the stability, conformational, and functional properties of protein structures. Surface hydrophobicity is the main physical parameter for evaluating proteins and it better reflects the interaction of proteins with water and other chemical groups 30 . The ANS fluorescence probe is a classical method to evaluate the surface hydrophobicity of proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Surface hydrophobicity is the main physical parameter for evaluating proteins and it better reflects the interaction of proteins with water and other chemical groups. 30 The ANS fluorescence probe is a classical method to evaluate the surface hydrophobicity of proteins. It is a reflection of the three-dimensional structure of proteins in an aqueous solution.…”
Section: Surface Hydrophobicity (H0)mentioning
confidence: 99%
“…The authors reported an improvement in the rheological properties and higher water‐holding capacity (>98%) for TGase‐induced gels. For TGase‐treated SPI, 7S, and 11S, sulfhydryl and surface hydrophobicity were lower; conversely, both the DH and the β‐sheets contents were increased significantly (Huang, Sun, Zhao, He, Liu, & Liu, 2022). Luo et al (2019) observed more resistance to deformation of the gels when SPI emulsions were treated with low TGase concentrations (1 and 3 U/g protein) prior to the gelation.…”
Section: Enzymatic Modificationsmentioning
confidence: 99%
“…Therefore, proteins with higher lysine and glutamine contents are potentially more favorable substrates for the TGase enzyme. These cross‐linking reactions promote the chemical bonding of adjacent protein molecules and form a new tertiary network structure, which can improve the water‐binding capacity, stability, and mechanical properties of the proteins (Huang, Sun, Zhao, He, Liu, & Liu, 2022). Glusac et al (2020) evaluated the effects of TGase on the digestibility and physical stability of chickpea protein isolate (CPI)‐stabilized o/w emulsions.…”
Section: Enzymatic Modificationsmentioning
confidence: 99%
“…1A and B). The polarity of the environment surrounding the SPI was changed by the urea molecules, resulting in protein swelling, hydrogen bond breakage, and a signi cant increase in average particle size (Huang et al, 2022). Previous studies have shown that the hydrogen bonds of soy peptide nanoparticles are disrupted by urea leading to an increase in their average particle size (Zhang et al, 2018).…”
Section: Spi-sa6 Stability Analysismentioning
confidence: 99%